Portfolio Optimization under ESG Constraints: Markowitz Model vs. Index Model - Wu Mengjie (SHS Web of Conferences, 2025)
This study addresses how to optimize portfolios under ESG constraints and short position constraints and explores the trade-off between sustainable investing and financial performance. This study is significant as it provides some new ideas and insights for improving sustainable finance by providing insights into how ESG factors affect portfolio construction and risk management to drive the development of sustainable finance. In this study, the Markowitz Model (MM) and Index Model (IM) are used to construct the optimal portfolio of 10 stocks in the US market, and the constraints of banning short selling and ESG score restrictions are added. The results show that MM is more effective in integrating ESG constraints, which can improve the portfolio ESG score and reduce the exposure to high carbon emission industries, and is more suitable for investors who prioritize sustainability, while IM is more suitable for investors who adopt passive investment strategy. The study highlights the importance of incorporating ESG factors into portfolio optimization, providing some valuable ideas for institutions and investors in balancing financial returns with sustainable practices.